Cerebral angiography in brainstem revascularization. - Jack, C R; Boulos, R S; Mehta, B A; Bhansali, D; Ausman, J I; Diaz, F G; Patel, S C (American Journal of Neuroradiology, 1987)
Surgical management of patients with vertebrobasilar insufficiency has been developed within the past decade. Cerebral angiography plays a crucial role in identifying potential surgical candidates and in directing the surgical approach. Fifty-two patients underwent brainstem revascularization procedures at Henry Ford Hospital between November 1979 and August 1985. Twelve occipital artery to anterior inferior cerebellar artery bypasses, five occipital artery to posterior inferior cerebellar artery bypasses, four intracranial vertebral endarterectomies, 29 superficial temporal to superior cerebellar artery bypasses, and two superficial temporal to posterior cerebral artery bypasses were performed. The preoperative angiograms in these patients were analyzed to illustrate how angiographic localization of vascular disease directs the surgical approach. We report the results of postoperative angiograms. Technical features of the various surgical procedures, the role of the neuroradiologist, and several features of the angiographic technique used with these patients are described.